Pendampingan Penanaman Karakter Saling Menghargai Melalui Duta Anti Bullying untuk Siswa Sekolah Dasar di Kabupaten Situbondo - Heldie Bramantha; Mufarrahatus Syarifah (LPPM UNINUS, 2017)
This activity aims to provide a new understanding of social patterns that have been prevalent in the middle of elementary students. Through the elected and trained “duta anti bullying